The Effect of a Scientific Approach on Motivation to Learn Morals at MA Salafiyah - Uun Unariah; Siti Maryam Munjiat (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
The number of students who do not actively participate in the teaching and learning process, such as rarely asking questions or voicing ideas, and also not reacting to the teacher's answers, one of the triggers is that the learning approach in Aqidah Akhlak subjects focuses more on teachers lecturing students and telling stories so that learning activities tend to be mainly carried out by teachers even though an educator plays a vital role in the achievement of an effective learning process. This study aims to analyze the effect of scientific methods on increasing student interest in learning aqidah subjects. By using a quantitative descriptive method through a saturated sampling technique involving 30 students with pree-test and post-test with sig value indicator 0.05 along with hypothesis testing and resulting in the conclusion that Ha is accepted and Ho is rejected based on the influence of scientific methods on learning motivation (tcount> ttable, namely 4.760> 2.048). This shows that learning motivation is strongly influenced by scientific-based learning. Although 55.3% of the influence is caused by causes other than the desire to learn, 44.7% of the influence is of high quality. From the determination test data, it can be concluded that the scientific method influences learning motivation.